Asia's middle-income challenge: An overview - Gemma Estrada; Xuehui Han; Donghyun Park; Shu Tian (Asian Development Bank (ADB), 2017)
Developing Asia has undergone a dramatic shift over the past 5 decades from a region of mainly lowincome economies toward one that is largely middle income. Compared with world aggregate data, developing Asia now has a much greater proportion of middle-income economies. The region faces the challenge of sustaining rapid growth after graduating from low to middle income, and moving further to high income. Evidence shows that it takes longer for economies to move from upper-middle to high income than shifting from lower-middle to upper-middle income. Still, developing Asian economies were able to shift more quickly than the rest of the world, whether the transition is from lower-middle to upper-middle income or from upper-middle to high income. The experience of newly industrializing economies shows that innovation, human capital, and infrastructure all played a vital role in their quicker transformation from middle to high income.
Keywords: O10; O11; 330; Asia; economic growth; middle income